Making marriages last: Trust is good, but credible information is better - Rebecca L. Thornton; Hans-Peter Kohler (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
In high HIV-prevalence contexts, marriage can lead to significant risks through spousal behaviours. Yet, individuals cannot rely on their spouse to reveal their HIV status. Couples' HIV testing and counselling can provide spouses with credible information about each other's HIV status. Using random variation in participation in couples' testing, this study documents that uncertainty about spouses' HIV status contributes to marital dissolutions. Innovations, such as HIV couples' testing and counselling - and, in the future, possibly rapid self-testing - that reduce this uncertainty can thus have profound impacts on marital behaviours and stability.
Keywords: C93; I12; I30; 330; HIV prevention; field experiment; subjective beliefs; uncertainty